Development and evaluation of 6-mercaptopurine and metoclopramide polypill formulation for oral administration: In-vitro and ex vivo studies - Chowdhary, Rajani; Pai, Roopa S; Singh, Gurinder (International Journal of Pharmaceutical Investigation)
Introduction: The present investigation was to develop a polypill of 6-mercaptopurine and metoclopramide. A polypill with delayed release granules of an anticancer and immediate release mucoadhesive tablet of antiemetic may result in the reduction of emesis caused by oral chemotherapy. Materials and Methods: 6-Mercaptopurine granules were prepared by wet granulation process. Chitosan, hydroxypropyl methylcellulose, and ethylcellulose were used as individually as delayed release polymers. Seven granule formulations (F1-F7) were prepared and evaluated for flow properties and drug content. Immediate release mucoadhesive tablets of metoclopramide were prepared by direct compression technique using pectin and PVPK-40 as mucoadhesive polymers. Three formulations of pectin (L1-L3) and three formulations of PVPK40 (M1-M3) were prepared using lactose, magnesium stearate, and mannitol and talc as diluent and glidant, respectively. Tablets were evaluated for weight variation, hardness, friability, drug content, ex vivo mucoadhesion time, and in vitro dissolution studies. Results: Formulation F2, F4, F5, and F7 showed maximum drug content. Formulation F7 exhibited the drug release up to 2 h and was selected as the best delayed release formulation. All formulations of metoclopramide showed good drug content ranging from 97.6 % to 100.6%. Formulation M2 among tablets prepared with PVP exhibited desired mucoadhesion time of 15.33 min which prolongs the duration of drug release in gastric pouch of the male Wistar rats. Both the selected formulations F7 and M2 were filled into body of capsule size 0 and capsule was evaluated for technological properties. Conclusion: It may be concluded that polypill released the metoclopramide immediately prior to 6-mercaptopurine.
Keywords: 6-mercaptopurine; delayed release; immediate release; metoclopramide; polypill